Analysis the structural complexity of “Time” in Hans Zimmer’s score for ”Inception” - Sandi Putra Ikhsan; Hafizhah Insani Midyanti (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
This study explores the intricate structure of "Time", a piece in Hans Zimmer's. The study aims to analyze the complex layers of "Time" and its influence on the overall impression of the picture. The primary study question investigates how the structural components of the composition, such as its recurring motifs, slow progression, and emotional climaxes, correspond to and amplify the movie's examination of time and reality. The process entails a qualitative analysis utilizing a literature review and an observational assessment of the film's audio-visual synchronization. By analyzing scholarly publications and conducting a literature study, the research reveals how Zimmer's minimalist approach and his inventive utilization of electronic sounds produce a distinctive auditory encounter that reflects the film's themes. Examining pivotal scenes that prominently display the concept of "Time" allows us to understand the intentional decisions made in the composition and execution of the music. The research findings indicate that the intricate composition of "Time" greatly amplifies the viewer's sense of being fully engaged in the film. The changing dynamics and recurring patterns of the piece not only mirror the emotional progress of the characters but also act as a guiding force for the viewer, helping them navigate through the complex storyline of the film. The emotional trajectory depicted in "Time"—evolving from a state of tension and confusion to one of resolution and hope—mirrors the thematic trajectory of the film, emphasizing its crucial function as an integral element in the narrative process. This analysis illustrates that the popularity of "Inception" is not exclusively attributed to its visual and narrative originality but is equally ascribed to its refined utilization of music. "Time" demonstrates how film music may significantly impact the audience's emotional and intellectual involvement, solidifying its position as a significant piece in modern cinema.